The house on the cliff - Dixon, Franklin W. (Dixon, Franklin W. Hardy boys mystery stories, 1987)
When Mr. Hardy disappears while investigating a mystery surrounding a vacant house rumored to be either haunted or an abode for criminals, the Hardy Boys search for the truth.